Unpacking the Past and Charting the Future: A Comprehensive Review of Organizational Development Trends and Predictions - Patangia, Bishal; R, Vijaya (Ushus Journal of Business Management, 2023)
The current study is a comprehensive review that provides an overview of recent trends in Organizational Development (OD) over the past five years (2018-23) based on empirical evidence. The study analyzes the identified trends, key concepts, and theories, and their impact on the OD field. The major trends in OD identified include strategic agility, learning and development, digital transformation, effective leadership, engagement and well-being, and fostering inclusivity and diversity. The study highlights the underlying theories and approaches that have influenced these trends. The findings suggest that organizations need to adapt to change faster with a dynamic environment and market expectations, and strategic agility is crucial for researchers and business practitioners. Learning and development within the organization is essential to keep employees up-to-date with relevant skills and help them adapt to changes much faster. Effective leadership, engagement and well-being, and fostering inclusivity and diversity are also critical for organizational growth and sustainability. The study provides insights for OD professionals to tailor solutions that meet the unique requirements of each organization and forecasts the future of OD globally by identifying trends and emerging issues.